Implementation Of Interpersonal Communication In Maintaining Family Harmony - Fauzan Amrullah; Muhammad Alfikri (IHSA Institute, 2022)
The purpose of this research is to determine how interpersonal communication contributes to family harmony. Family harmony must be maintained so that there is no normative violation and divorce does not occur. This study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. The findings revealed three patterns of interpersonal communication in maintaining family harmony: 1) speaking, 2) listening, and 3) empathizing. These three factors play an important role in maintaining family harmony so that children feel loved and obey their parents' words. Parents play an important role in establishing interpersonal communication so that no more children engage in harmful behaviors that violate norms. Furthermore, several points must be maximized in order for the family to remain harmonious.